Grass-legume intercropping helps in livestock development - Kumar, Sushil; Machiwal, Deepesh (Indian Farming, 2018)
The performance of grasses and legumes in intercropping over its sole counterparts for the enhanced quality fodder production in the arid region of Kachchh, India was studied. The results showed that without adding any extra inputs cost on resource poor farmers of arid eco-system, intercropping of grass-legume yielded more quality fodder over its sole counterparts. Thus, it may be said that grass-legume intercropping system may be the best viable option for enhanced quality fodder production for the arid condition of the Kachchh for overall development of livestock sector. The findings of the study are applicable to all the arid regions of the world because enhanced quality fodder is main requirement for the arid system, wherein agriculture systems are livestock-centric and livestock remains main source of livelihood for the inhabitants.